Enhancing physical fitness through school-based morning exercise: an experimental study among children aged 10–12 years - Hasmara, Puguh Satya; Ma'arif, Ilmul; Yudi Dwi Saputra (Physical Education Departement of University PGRI Jombang, 2025)
The declining level of physical activity among elementary-school children has become a major health and educational concern, as it contributes to reduced physical fitness, increased sedentary behavior, and lower learning readiness. This study aims to analyze the effect of a structured school morning-exercise intervention on the physical fitness of children aged 10–12 years. A quantitative experimental method using a pretest–posttest control-group design was applied to 120 students from SD Negeri Bakalan, SD Negeri Centong, SD Negeri Warugunung, and SD Negeri Pandan in Kabupaten Mojokerto. The experimental group participated in an eight-week morning-exercise program held three times per week, while the control group continued regular school activities. Data on five physical-fitness components—40 m run, sit-up, vertical jump, 600 m run, and sit-and-reach—were collected using the Tes Kebugaran Jasmani Indonesia (TKJI). Statistical analysis using paired- and independent-sample t-tests revealed significant improvements (p < 0.05) in all components, with medium effect sizes (Cohen’s d ≈ 0.6). The findings confirm that structured rhythmic exercise effectively enhances speed, strength, endurance, and flexibility. This research concludes that school morning exercise is an efficient, low-cost, and sustainable strategy for improving physical fitness and supporting learning readiness. The study contributes to the advancement of evidence-based school health promotion aligned with SDG 3 (Good Health and Well-Being) and SDG 4 (Quality Education), and recommends future research on its long-term cognitive effects